Value stream mapping implementation in a small and medium agro-based industry - Ahmad Hafizzudin, Ahmad; Nik Mohd Zuki, Nik Mohamed; Fazilah, Abdul Aziz (Penerbit UMP, 2024)
This study explores the implementation of Lean Manufacturing Systems at a small and medium-sized enterprise (SME) in the agro-industrial sector to identify and eliminate potential waste. The study analyzes current operational inefficiencies and proposes effective Lean solutions. Data on the company's production processes were collected and analyzed to pinpoint sources of waste. Using Tecnomatix Plant Simulation software, models of the current and improved future states were developed. These models provided a detailed visualization of the process flow, identifying key areas where Lean interventions could yield significant improvements. The effectiveness of these Lean initiatives was further analyzed using Value Stream Mapping (VSM), which facilitated a comparative analysis of process performance before and after implementing Lean improvements. The results demonstrated substantial enhancements in operational efficiency, which is 20.7%, doubled the profits, and improved customer satisfaction. This study not only underscores the feasibility of applying Lean principles in SME but also provides a robust framework for other similar enterprises to follow. The findings and recommendations presented in this study offer SME a strategic approach to achieving sustainable operational improvements and competitive advantage in their respective markets.